FcRn-enhancing mutations lead to increased and prolonged levels of the HIV CCR5-blocking monoclonal antibody leronlimab in the fetuses and newborns of pregnant rhesus macaques - Joanna Zikos; Gabriela M. Webb; Helen L. Wu; Jason S. Reed; Jennifer Watanabe; Jodie L. Usachenko; Ala M. Shaqra; Celia A. Schiffer; Koen K. A. Van Rompay; Jonah B. Sacha; Diogo M. Magnani (mAbs)
Prenatal administration of monoclonal antibodies (mAbs) is a strategy that could be exploited to prevent viral infections during pregnancy and early life. To reach protective levels in fetuses, mAbs must be transported across the placenta, a selective barrier that actively and specifically promotes the transfer of antibodies (Abs) into the fetus through the neonatal Fc receptor (FcRn). Because FcRn also regulates Ab half-life, Fc mutations like the M428L/N434S, commonly known as LS mutations, and others have been developed to enhance binding affinity to FcRn and improve drug pharmacokinetics. We hypothesized that these FcRn-enhancing mutations could similarly affect the delivery of therapeutic Abs to the fetus. To test this hypothesis, we measured the transplacental transfer of leronlimab, an anti-CCR5 mAb, in clinical development for preventing HIV infections, using pregnant rhesus macaques to model in utero mAb transfer. We also generated a stabilized and FcRn-enhanced form of leronlimab, termed leronlimab-PLS. Leronlimab-PLS maintained higher levels within the maternal compartment while also reaching higher mAb levels in the fetus and newborn circulation. Further, a single dose of leronlimab-PLS led to complete CCR5 receptor occupancy in mothers and newborns for almost a month after birth. These findings support the optimization of FcRn interactions in mAb therapies designed for administration during pregnancy.